Stacked traits conferring multiple resistance to imazamox and glufosinate in soft wheat - Dominguez-Mendez, Rafael (2019)
BACKGROUND Conventional crossing of soft wheat cultivars resistant to imazamox and glufosinate resulted in two (Rados and Helter) lines resistant to both herbicides. Stacked traits conferring this dual herbicide resistance in these lines, compared with a susceptible (S) cultivar, were characterized. RESULTS Rados and Helter lines were ∼ 18‐fold more resistant (R) to glufosinate, and between 15.1 and 19.8‐fold more resistant to imazamox than the S cultivar. Resistance to glufosinate and imazamox decreased up to 12% and 50%, respectively, when the herbicides were applied sequentially. The basal activities of the acetolactate and glutamine synthases were similar between R and S plants. Rados and Helter lines were 11.7‐ and 17.7‐fold more resistant to imazamox than the S cultivar, due to the Ser653–Asn mutation in their imi‐ALS genes. R lines, susceptible to glufosinate at the target site level, showed lower ammonia accumulation evidencing the activity of the phosphinothricin acetyl transferase. Absorption and translocation patterns for 14C‐imazamox and 14C‐glufosinate were similar between R and S cultivars and so do not contribute to resistance. CONCLUSION Stacked traits conferring dual herbicide resistance to the lines Rados and Helter come from the resistant parents. These R lines are potential tools for weed management in wheat production, mainly via herbicide rotation. © 2018 Society of Chemical Industry